Inovasi Pembiayaan Perguruan Tinggi: Diversifikasi Sumber Daya dan Keberlanjutan Institusi: Innovation in Higher Education Financing: Resource Diversification and Institutional Sustainability - Sri Hayati; Anastasia Hiyang; Widyamitke Gede Mulawarman (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Financing higher education in Indonesia faces increasingly complex challenges due to limited public budgets, rising operational costs, and demands for equitable access and improved educational quality. In the context of higher education autonomy, particularly for State-Owned Legal Entities (PTN-BH), institutions are required to develop innovative and sustainable financing strategies to reduce dependence on government funds and the Single Tuition Fee (UKT). This study analyzes innovative models for financing higher education through resource diversification and their implications for institutional sustainability and educational accessibility. The research method is a qualitative case study, with data collected through a review of policy documents and university financial reports, as well as in-depth interviews with key stakeholders, including university leaders, alums, and private-sector partners. The results show that implementing a hybrid financing model that integrates research commercialization and endowment fund management can enhance universities' financial independence without compromising their social mission. The success of this model is supported by regulatory autonomy, professional governance, and the application of transparency and accountability principles in financial management. Furthermore, revenue from non-UKT sources has been shown to contribute significantly to scholarship funding, cross-subsidies, and the stabilization of education costs, thereby expanding access for students from disadvantaged backgrounds. This study concludes that financing innovation is a strategic key to achieving financial sustainability and equitable access to higher education in Indonesia, and that this requires an adaptive regulatory framework and the continuous strengthening of institutional managerial capacity.